Toxicity of different classes of manufactured naomaterials in alveolar epithelial cells - Brandão, Fátima (2019)
The toxicological assessment of the potential toxicity of manufactured nanomaterials (MNMs) is urgently needed due to their increased use for commercial and industrial applications. Thus, this study evaluated the cyto- and genotoxicity of a panel of MNMs, including SiO2 NPs, graphene oxide, and nano-sized pigments in rat alveolar epithelial cells (RLE-6TN), a primary target during inhalation exposure.